Aeolian dust deposition in the southern Aral Sea region (Uzbekistan): Ground-based monitoring results from the LUCA project. (30th January 2017) - Opp, Christian; Groll, Michael; Aslanov, Ilkhom; Lotz, Tom; Vereshagina, Nataliya
Abstract: As larger parts of the former Aral Sea have been desiccated, more (and harmful) dust storms (DS) and dust deposition (DD) occur more frequently in the surrounding area. Due to the prevalent wind directions, the southern Aral Sea region is affected stronger by these DS and DD as other areas around the former Aral Sea. The densely populated study area belongs to the autonomous republic of Karakalpakstan and the autonomous oblast (district) Khorezm within the Republic of Uzbekistan. For improving the knowledge about the spatial and temporal distribution of DD in the study region, seven sampling stations of the Uzbek meteorological survey have been equipped with passive deposition samplers between 2003 and 2012. The monthly amount of dust, the grain sizes, the mineralogical and chemical composition were determined and in several cases individual dust storm events were analyzed as well. Although the monthly average dust deposition was relatively low (598.4 kg/ha), the peak deposition during dust storms was up to 160 times higher than this average. While the seasonal DD rate was increasing from spring to fall, the health related threshold excess showed the highest intensity during spring and summer. At most stations the grain size composition of the dust samples (85–90% are silt and clay dominated) was very similar to the composition of the near surface soils. The stations Muynak and Jaslyk, representing dust originating from the Aral Kum, are characterized by dust rich in HCO3, SO4 and Ca. Among the trace elements, heavy metals were analyzed because of their health-affecting potential. The total heavy metal concentrations in the southern Aral Sea region are relatively low compared to the results from other parts of Uzbekistan. Zinc showed the greatest dominance close to the Aral Kum, while chromium on the other hand increased its percentage with a growing distance to the former Aral Sea. The spatial and temporal dynamics of the dust deposition as well as the distribution of heavy metals indicate a further need for ground based research for the improvement of the database and a better understanding of the dust mobilization, transport and deposition mechanisms in the Aral Kum and the southern Aral Sea region.